PELATIHAN PEMBUKUAN SEDERHANA DI WARUNG PAK NARDI DAN WARUNG ANANDA - Elfridus Wahyudi; Martinus Budiantara (JURNAL PENGABDIAN MANDIRI, 2023)
Micro, small, and medium enterprises (MSMEs) play a pivotal role in driving Indonesia's economy, particularly in the context of small food stalls and shops serving as the backbone of local economies. Despite their significance, many micro and small business owners face challenges in financial management, specifically in proper bookkeeping and accurate financial reporting. This study focuses on two small food stalls, Warung Pak Nardi and Warung Ananda, in Sleman Regency, Yogyakarta, aiming to address the main challenges in implementing simple bookkeeping practices. The participatory research approach involves training sessions covering the basics of simple bookkeeping, practical exercises in daily financial recording, assistance in creating simple financial reports, and continuous monitoring and feedback. The results indicate a positive impact on financial management, operational efficiency, and profitability in both stalls. The improved understanding of bookkeeping enhances decision-making and financial health. This training approach holds potential to enhance financial well-being and sustainability for micro-level MSMEs.